Carolina Martínez S. Sobrevivir en Malinalco : la salud al margen de la medicina. México : El Colegio de México : Universidad Autónoma Metropolitana-Xochimilco, 1993 - Tuirán, Rodolfo (Estudios Demográficos y Urbanos, 1993)
Carolina Martínez S., Sobrevivir en Malinalco. La salud al margen de la medicina, México, El Colegio de México y Universidad Autónoma Metropolitana-Xochimilco, 1993.